Antidiabetic and renoprotective effects of Corni Fructus extract in db/db mice - Kim, Hye-Jeong; Kim, Young-Chul (Molecular & cellular toxicology, 2010)
This study investigated the effect of Corni Fructus ( Cornus officinalis Sieb. et Zucc.) extract on hyperglycemia, renal dysfunction and diabetic nephropathy in db/db mice. Eight weeks old male mice were divided into normal control group (NC), diabetic control group (DC) and Corni Fructus treated diabetic group (DCF). Over an 8-week experimental period, Corni Fructus extract was administered orally at 500 mg/kg BW/day. Final fasting serum glucose level in the DCF group was significantly lower than the DC group by 32% ( P <0.05). Urine 24-h volume and urine total protein in the DCF group were significantly lower ( P <0.05) than the DC group by 53% and 88%, respectively. The mRNA expression of angiotensin II, collagen I, collagen IV and TGF-β 1 in kidneys were significantly lower ( P <0.05 or P <0.01) in the DCF group than the DC group by 39%, 42%, 38% and 26%, respectively. In histological staining of kidney tissues, collagen deposition was markedly reduced in the DCF group compared to the DC group. Immunohistochemical staining for TGF-β 1 in kidneys of the DCF group was more mildly expressed than the DC group. In conclusion, these results indicate that Corni Fructus can be effective on hyperglycemia, renal dysfunction and diabetic nephropathy in db/db mice.